Perspectives for nano-biotechnology enabled protection and nutrition of plants - Ghormade, Vandana; Deshpande, Mukund V.; Paknikar, Kishore M. (Biotechnology Advances, 2011)
Indiscriminate use of pesticides and fertilizers causes environmental pollution, emergence of agricultural pests and pathogens, and loss of biodiversity. Nanotechnology, by virtue of nanomaterial related properties, has potential agro-biotechnological applications for alleviation of these problems. The literature pertaining to the role of nanotechnology in plant and soil systems demonstrates that nanomaterials may assist in a) the controlled release of agrochemicals for nutrition and protection against pests and pathogens, b) delivery of genetic material, c) sensitive detection of plant disease and pollutants and d) protection and formation of soil structure. For instance, porous silica (15 nm) and biodegradable, polymeric chitosan (78 nm) nanoparticles displayed slow release of encapsulated pesticide and fertilizer, respectively. Further, nanosized gold (5-25 nm) delivered DNA to plant cells while iron oxide (30 nm) based nanosensors detected pesticides at minute levels. These functions assist the development of precision farming by minimizing pollution and maximizing the value of farming practice. (C) 2011 Elsevier Inc. All rights reserved.
Keywords: Biofertilizer; Biopesticides; Controlled delivery; Fertilizer; Genetic material; Nanomaterials; Nanosensors; Pathogen; Pesticides; Residues